Timer-Based Capacitance-to-Voltage Converter - Kaewpoonsuk, Anucha; Tokampang, Sudarat; Sisuk, Noppadon; Rerkratn, Apinai; Petchmaneelumka, Wandee (My University, 2026)
This article presents the design and analysis of a capacitance-to-voltage converter based on 555-timer Integrated Circuits (ICs) as the core design element. The circuit structure consists of two primary active components: two 555-timer ICs connected in conjunction with a low-pass filter circuit. The first 555-timer IC operates in astable mode to generate a signal that controls the timing of the second IC. The target capacitor or capacitive sensor to be measured is connected to the second 555-timer IC, which operates in monostable mode. The output signal from the second 555-timer IC is then converted into a DC voltage output using a low-pass filter circuit. The circuit was tested using laboratory capacitors in the range of 52.72 pF to 807.61 pF, and the data were analyzed using Microsoft Excel. The results showed excellent agreement with the measurements obtained from the GW INSTEK LCR-819. The maximum uncalibrated error was found to be −3.32% of full scale. After applying linear curve fitting in Excel, the maximum error was reduced to 0.92% of full scale, confirming the effectiveness of the calibration approach. Furthermore, the circuit was applied to measure the moisture content of paddy rice using a cylindrical capacitive sensor within the moisture range of 12.1% to 23.2%. The experimental data were fitted to a derived equation, which was then used to predict rice moisture content, producing results that corresponded closely with those obtained from the KETT PM-450 grain moisture meter.
Keywords: 555-timer; Capacitance-to-Voltage Converter (CVC); capacitive readout circuit; capacitive sensor